Lage landen, verre horizonten. De verbinding van natuur, landschap en ’Nederlandse’ identiteit in internationaal perspectief - Davids, K. (BMGN - Low Countries Historical Review, 2006)
Karel Davids, Low countries, faraway horizons. The relation between nature, landscape and ‘Dutch’ identity in a comparative perspectiveHow did nature, landscape and identity in the Netherlands become intertwined during the course of the nineteenth and twentieth centuries? And more particularly, how was this development linked up with changes in the relationship between the Netherlands and other parts of the globe? These are the key questions addressed in this essay. The article argues that the growing interconnection between nature, landscape and identity can only partly be explained by home-grown traditions, such as the increased cooperation between science and capital or the presence of a highly developed art of landscape painting. In many respects, developments in the Netherlands showed in fact striking parallels and connections with developments in other areas of the world. Numerous elements in the newly-emerged view of nature and landscape were adopted from abroad and Dutchmen ardently projected their own national ambitions and pretensions in confrontations with wild nature and foreign rivals outside their territory along the North Sea. Thus, the `Dutch’ identity was also constructed in the jungle of the East-Indies and the thin air of the Alps. This article is part of the special issue 'Landschap, natuur en nationale identiteit'.